Design of a selective filter - antenna with low insertion loss and high suppression stopband for WiMAX applications - Alkhafaji, M. K.; Sahbudin, R. K. Z.; Ismail, A. B.; Hashim, S. J. (2016)
This paper presents a selective quasi–elliptic bandpass filter-antenna. The presented filter-antenna has a low insertion loss in the passband and relatively high stopband rejection. This structure consists of a quasi–elliptic bandpass filter direct coupled with patch antenna. The bandpass filter consists of four (λ/4) spiral square resonators. It has operates between (3.25–3.6) GHz so it is suitable for WiMAX applications. A CST Microwave Studio Suite software has used to simulate the filter-antenna circuit. The simulated results of the patch antenna and the results of the filter-antenna appears a good matching between the two circuits.